Contrasting HIV prevalence trends among young women and men in Zambia in the past 12 years: data from demographic and health surveys 2002–2014 - Chola Nakazwe; Charles Michelo; Ingvild F. Sandøy; Knut Fylkesnes (BMC Infectious Diseases, 2019)
Abstract Background The HIV epidemic remains a concern on the global health agenda, despite progress made in reducing incidence. Investigation of trends among young people is important for monitoring HIV incidence and informing programming. The study examined geographical and sub-population differences in HIV prevalence trends among young people aged 15–24 years in Zambia. Methods This study analysed data from Zambia Demographic and Health Surveys (ZDHSs) that were conducted in 2001–2, 2007, and 2013–14. A two-stage cluster stratified sampling procedure was used to select samples of 8050, 7969, and 18,052 for the three surveys, respectively. Young people (15–24 years) with known HIV status were selected for analysis. The outcome variable was HIV status. Log binomial regression analysis of generalised linear models was used to test for trends. Results Overall HIV prevalence declined over the period 2001–2 to 2013–14 among women and men aged 15–49 years (17.8 and 12.9% to 15.1 and 11.3%, respectively). There was, however, an increase in HIV prevalence among urban young men over this period, from 3.7% in 2001–2 to 7.3% in 2013–14 (aRR 2.17, 95% CI 0.99˗4.75), and, in rural areas, from 2.6 to 3.6% (aRR 1.46, 95% CI 0.78˗2.75). In contrast, HIV prevalence among women declined over the same period of time. In urban areas, HIV prevalence among women declined from 15.2 to 10.7% (aRR 0.66, 95% CI 0.53˗0.93), while in rural areas it declined from 8.2 to 4.8% (aRR 0.41, 95% CI 0.59˗0.85). In addition, there was a narrowing gender gap in terms of HIV infection, as the prevalence ratio of females to males declined from 4.2 and 3.1 to 1.5 and 1.3, in urban and rural areas, respectively. Conclusions The increase in HIV prevalence among urban young men over the past 12 years, contrasting declining trends among young women in both urban and rural populations, suggests differential effects of prevention efforts. Furthermore, findings that Zambia’s overall national HIV prevalence decline masks some striking sex and rural/urban differentials, indicate the need for reconsidering the prevention efforts for young urban men.